Quercetin Encapsulation on Chitosan-Pectin Membranes as a Drug Delivery and Its Release Kinetics - Hastuti, Budi; Hadi, Saptono; Nisriyah, Safarin; Martanisa, Mutiah; Kamari, Azlan (BRIN Publishing (Penerbit BRIN), 2025)
Chitosan-pectin membranes are biodegradable polyelectrolyte complexes, derived from biomaterials, with good stability for drug delivery applications. This study investigates the potential of these membranes to encapsulate quercetin, a flavonoid known for its therapeutic properties but limited for its low solubility, poor bioavailability, and rapid elimination. The membranes were synthesized using a 1:1 (w/w) chitosan-to-pectin ratio and loaded with quercetin via solvent evaporation. Characterization using FTIR confirmed the presence of OH, C=O, and NH groups; XRD indicated semi-crystalline structure; and SEM revealed a uniform, porous morphology. The maximum quercetin loading efficiency reached 82.43%, with the highest release (90.39%) observed at pH 1.2, following first-order kinetics. The resulting membrane was thin, brown, homogeneous, and tear-resistant, demonstrating its potential as a controlled drug delivery matrix for quercetin